The Gilding-the-Lily Effect: Exploratory Behavior Energized by Curiosity - Shen, Mowei; Liu, Pengpeng; Li, Xinyu; Zhou, Jifan; Chen, Hui (Frontiers in Psychology, 2020)
The widespread metaphor “to gild the lily” suggests that people usually engage in superfluous behaviors. Understanding the mechanism behind superfluous behaviors helps individuals reduce possible waste and even disaster incurred by unnecessary actions. Here, we assumed that curiosity for new information partly pushes people to make such unnecessary efforts. This hypothesis was tested through three experiments. In three experiments we found that when participants knew that expending more efforts than task requirements brought no better results, they still exerted various exploratory activities to fulfill curiosity. These results imply that the impulsion to satisfy the desire for information could partly push individuals to indulge in unnecessary activities beyond task demands. This improves the comprehension of irrational superfluous behavior and provides directions to reduce loss and waste caused by gilding the lily.